Dexmedetomidine is safe and effective for reducing intraprocedural pain in colorectal endoscopic submucosal dissection. Issue 1 (27th March 2023) - Iwagami, Hiroyoshi; Akamatsu, Takuji; Matsuyama, Kazuki; Hanawa, Yusuke; Tonomura, Kohei; Chikugo, Eiki; Ogino, Shinya; Morimura, Hiroki; Shimoyama, Masayuki; Terashita, Tomoko; Nakano, Shogo; Wakita, Midori; et al.
Abstract: Objectives: Endoscopic submucosal dissection (ESD) is effective for the resection of colorectal intramucosal lesions. This study was performed to examine the safety and effectiveness of using dexmedetomidine (DEX) in the anesthesia regimen of patients with colorectal lesions undergoing ESD. Methods: We retrospectively examined 287 consecutive patients who underwent ESD for colorectal lesions in our institution from January 2015 to December 2021. Outcomes including the frequency of intraprocedural pain and adverse events were compared between the DEX and no DEX groups. Moreover, univariate and multivariate analyses were conducted for each clinical factor of intraprocedural pain. Intraprocedural pain was defined as patient‐reported abdominal pain or body movement during the procedure. Results: The incidence of intraprocedural pain was significantly lower in the DEX than in the no DEX group (7% vs. 17%, p = 0.02). The incidence of hypotension was also significantly higher in the DEX group (7% vs. 0%, p = 0.01), but no cerebrovascular or cardiac ischemic events occurred. In the univariate analyses, the diameter of the resected specimen, procedure time, no use of DEX, and total midazolam dose was associated with intraprocedural pain. The midazolam dose and DEX administration were significantly negatively correlated and the diameter of resected specimen and procedure time were significantly positively correlated. Multivariate logistic regression showed that no use of DEX was independently associated with intraprocedural pain ( p = 0.02). Conclusions: Adding DEX to the anesthesia regimen in patients undergoing colorectal ESD appears to be safe and effective for reducing intraprocedural pain.